2009
DOI: 10.3171/2008.11.spi08615
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical discectomy and fusion with structural allograft and plates for the treatment of unstable posterior cervical spine injuries

Abstract: Object The purpose of this study was to evaluate complications and radiographic and functional outcomes of isolated anterior stabilization surgery in which structural allograft and plates were used for posterior unstable subaxial cervical spine lateral mass, facet, and ligamentous injuries. Methods Between August 2003 and January 2008, 19 consecutive patients with unstable lateral mass, facet, and/or pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 39 publications
0
22
0
2
Order By: Relevance
“…Woodworth et al report that 1 of 17 (5.8%) patients with posterior ligamentous injury treated with ACDF went on to a progressive kyphotic deformity. 12 The patient remained neurologically intact and fused in a kyphotic position and required no further treatment. In a retrospective review of patients who underwent treatment for flexion distraction injuries, Johnson et nal cord.…”
mentioning
confidence: 86%
“…Woodworth et al report that 1 of 17 (5.8%) patients with posterior ligamentous injury treated with ACDF went on to a progressive kyphotic deformity. 12 The patient remained neurologically intact and fused in a kyphotic position and required no further treatment. In a retrospective review of patients who underwent treatment for flexion distraction injuries, Johnson et nal cord.…”
mentioning
confidence: 86%
“…There is still a lack of guidance for using the anterior, posterior, or combined surgical procedures. 34 Historically, surgical treatment was performed using posterior interspinous or 18 Several studies have also reported good clinical outcomes and high fusion rates in association with anterior discectomy, fusion, and plate fixation. 18 Kwon et al reported on a prospective randomized controlled study in which they compared anterior with posterior stabilization for unilateral facet injuries of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…34 In the Subaxial Injury Classification (SLIC) scale, translation or rotation injuries are assigned the highest number of points (4 points). 32 Significant ligament disruptions are almost always associated with injuries of the subaxial spine.…”
mentioning
confidence: 99%
“…Whereas most cervical subaxial trauma was treated by posterior approaches in the past, there is now significant evidence suggested that an anterior approach is similarly effective for stabilization. 24 The anterior approach is less traumatic and provides interbody grafting with reconstruction and maintenance of lordosis.…”
Section: Discussionmentioning
confidence: 99%